1995
DOI: 10.1002/chin.199512178
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: New Coumarin Derivatives: 2‐(N‐R‐Imino)‐2H‐1‐benzopyrans.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Later, Pechmann and Welsh [23] found that a coumarin derivative is formed when a mixture of phenol and malic acid is heated in the presence of concentrated sulphuric acid. In most cases, the synthesis of 2‐iminocoumarins is based on the Knoevenagel reaction between o ‐hydroxybenzaldehydes and aromatic or heteroaromatic compounds bearing a cyanomethyl substituent in the presence of organic bases [24–26]. This type of reaction is used mainly for preparation of 3‐substituted coumarins.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Pechmann and Welsh [23] found that a coumarin derivative is formed when a mixture of phenol and malic acid is heated in the presence of concentrated sulphuric acid. In most cases, the synthesis of 2‐iminocoumarins is based on the Knoevenagel reaction between o ‐hydroxybenzaldehydes and aromatic or heteroaromatic compounds bearing a cyanomethyl substituent in the presence of organic bases [24–26]. This type of reaction is used mainly for preparation of 3‐substituted coumarins.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few synthetic methods afford good yields of coumarin moieties. To synthesise 2‐iminocoumarins, the Knoevenagel reaction, between ortho ‐hydroxybenzaldehydes and a nitrile with an activated methylene group in the presence of organic bases, is the most common reaction [11–13]. This type of reaction is more often used to prepare other substituted coumarins.…”
Section: Introductionmentioning
confidence: 99%